2023
DOI: 10.1002/cb.2261
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating sustainable consumption: The role of harmonious cultural values and pro‐environmental self‐identity

Anita Lifen Zhao,
Janine Dermody,
Nicole Koenig‐Lewis
et al.

Abstract: This paper investigates the connections between harmonious cultural values, pro‐environmental self‐identity and consumers' sustainable consumption behaviours spanning acquisition, usage and disposal. It evaluates the relevance of Chinese cultural values that purport harmony between humans, nature and society that is, man‐nature orientation, and horizontal/vertical dimensions of individualism collectivism. The results from the online survey with 503 urbanised Chinese reveals these values disparately influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
(291 reference statements)
0
3
0
Order By: Relevance
“…Some authors argue that the fundamental common good of culture is linked to adopting more environmentally responsible behaviours. They believe that a strong sense of self-hood helps individuals feel connected to both nature and others, leading to a greater awareness of environmental issues (Zhao et al, 2023). Similarly, Alejandro García (2022) concluded that the traditional knowledge of indigenous cultures promotes a more harmonious relationship between the community and resources, derived from the love and respect they feel for nature.…”
Section: Problem Statementmentioning
confidence: 99%
“…Some authors argue that the fundamental common good of culture is linked to adopting more environmentally responsible behaviours. They believe that a strong sense of self-hood helps individuals feel connected to both nature and others, leading to a greater awareness of environmental issues (Zhao et al, 2023). Similarly, Alejandro García (2022) concluded that the traditional knowledge of indigenous cultures promotes a more harmonious relationship between the community and resources, derived from the love and respect they feel for nature.…”
Section: Problem Statementmentioning
confidence: 99%
“…More studies are needed on the association between ecological awareness and SC practices. Furthermore, they should examine the psychological, emotional and cognitive factors, social drivers and norms of SC (Hueppe & Zander, 2024;Jeong & Kim, 2024;Kaplan et al, 2024;Lim, 2024;Onel, 2024;Kang et al, 2024;Zhao et al, 2024).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…The special issue also calls for future researchers to utilise diverse methodologies, including longitudinal studies and advanced analytical techniques in the field of study, to collect more robust findings (Jeong & Kim, 2024;Shukla et al, 2024;Zhao et al, 2024) that could suggest direct implications for policymaking and industry practices (Hueppe & Zander, 2024;Lim, 2024;Shukla et al, 2024;Kang et al, 2024;Thaichon et al, 2024). 3) diverse psychological perspectives on SC, especially those from diverse consumers (Indian, Turkish, Americans, Taiwanese, Chinese, German).…”
Section: Future Research Directionsmentioning
confidence: 99%